Lending Policies of Financial Intermediaries Facing Credit and Funding Risk - DESHMUKH, SUDHAKAR D.; GREENBAUM, STUART I.; KANATAS, GEORGE (Journal of Finance, 1983)
ABSTRACT This paper compares the optimal lending decisions of financial intermediaries that differ in their risk exposure. All intermediaries are assumed to face a loan demand described by a random applicant arrival process with each applicant offering a unique risk‐adjusted rate of return; loan demand is therefore uncertain in both quantity and quality. The intermediaries differ in terms of their risk exposure because of disparate funding practices. Intermediaries functioning as brokers minimize their exposure by borrowing funds only as demand is realized, whereas those behaving as asset‐transformers borrow in advance of realizing loan demand, thereby maintaining a loanable funds inventory and sustaining the related exposure. The optimal sequential lending policy is shown to involve setting a credit standard that becomes stricter with the length of the intermediary's planning horizon and the volume of loans outstanding. Most importantly, it is shown that brokers adopt stricter credit standards than asset‐transformers and therby reduce their volume of lending.